Expression and distribution of key proteins of the endocannabinoid system in the human seminal vesicles. (8th August 2017) - Ückert, S.; la Croce, G.; Bettiga, A.; Albrecht, K.; Buono, R.; Benigni, F.; Kuczyk, M. A.; Hedlund, P.
Summary: The endocannabinoid system (ECS), comprising the cannabinoid receptors (CBR), their ligands, and enzymes controlling the turnover of endocannabinoids, has been suggested to be involved in male reproductive function. As information is scarce on the expression of the ECS in human male reproductive tissues, this study aimed to investigate by means of molecular biology (RT‐PCR) and immunohistochemistry/immunofluorescence the expression and distribution of CB1 and CB2, GPR55 (an orphan G protein‐coupled receptor that recognises cannabinoid ligands) and FAAH (isoforms 1 and 2) in the human seminal vesicles (SV). The specimens expressed PCR products corresponding to CB1 (66 bp), CB2 (141 bp), GPR55 (112 bp), FAAH1 (260 bp) and FAAH2 (387 bp). Immumohistochemistry revealed dense expression of CB1, CB2 and GPR55 located to the pseudo‐stratified columnar epithelium and varicose nerves (also characterised by the expression of vasoactive intestinal polypeptide and calcitonin gene‐related peptide). Cytosolic staining for FAAH1 and FAAH2 was seen in cuboidal cells of all layers of the epithelium. No immunoreactivity was detected in the smooth musculature or nerve fibres. CB1, CB2, GPR55, FAAH1 and FAAH2 are highly expressed in the human SV. Considering their localisation, the ECS may be involved in epithelial homeostasis, secretory function or autonomic mechano‐afferent signalling.